Democratizing entry: Banking deregulations, financing constraints, and entrepreneurship☆ - Kerr, William R.; Nanda, Ramana (Journal of Financial Economics, 2009)
We examine entrepreneurship and creative destruction following US banking deregulations using US Census Bureau data. US banking reforms brought about exceptional growth in both entrepreneurship and business closures. Most of the closures, however, were the new ventures themselves. Although we find evidence for the standard story of creative destruction, the most pronounced impact was a massive increase in churning among new entrants. We argue that creative destruction requires many business failures along with the few great successes. The successes are difficult to identify ex ante, which is why democratizing entry is an important trait of well-functioning capital markets.